T1 Relaxation Measurement of Ex-Vivo Breast Cancer Tissues at Ultralow Magnetic Fields. (29th January 2015) - Lee, Seong-Joo; Shim, Jeong Hyun; Kim, Kiwoong; Hwang, Seong-min; Yu, Kwon Kyu; Lim, Sanghyun; Han, Jae Ho; Yim, Hyunee; Kim, Jang-Hee; Jung, Yong Sik; Kim, Ku Sang
Abstract : We investigated T 1 relaxations of ex-vivo cancer tissues at low magnetic fields in order to check the possibility of achieving a T 1 contrast higher than those obtained at high fields. The T 1 relaxations of fifteen pairs (normal and cancerous) of breast tissue samples were measured at three magnetic fields, 37, 62, and 122  μ T, using our superconducting quantum interference device-based ultralow field nuclear magnetic resonance setup, optimally developed for ex-vivo tissue studies. A signal reconstruction based on Bayesian statistics for noise reduction was exploited to overcome the low signal-to-noise ratio. The ductal and lobular-type tissues did not exhibit meaningful T 1 contrast values between normal and cancerous tissues at the three different fields. On the other hand, an enhanced T 1 contrast was obtained for the mucinous cancer tissue.